Local Excision of a Mucinous Adenocarcinoma of the Anal Margin (Extramammary Paget’s Disease) and Reconstruction with a Bilateral V-Y Flap - Michele Pagnanelli; Paola De Nardi; Stefano Martella; Luca Caruso; Riccardo Rosati (Case Reports in Surgery)
The case of a 75-year-old female with invasive extramammary Paget’s disease of the anal margin, without involvement of the anal canal, is reported. The patient underwent wide local excision of the lesion with reconstruction with a double V-Y flap, a biopsy of the inguinal sentinel node, and a laparoscopic temporary colostomy. No guidelines exist on the treatment of this rare disease, and both wide local excision and abdominoperineal resection have been proposed. In the present case, the absence of invasion of the anal canal, also confirmed by intraoperative biopsies on the resection margins, and of local lymph node metastasis, as confirmed by the sentinel lymph node biopsy, allowed a sphincter-sparing operation with good functional and oncological results.